The Iraq effect : the Middle East after the Iraq War - Wehrey, Frederic M. (Rand Corporation monograph series., 2010)
The conflict in Iraq has reverberated across the Middle East, affecting the balance of power between neighboring states, their internal political dynamics, how their publics view American credibility, and the strategies and tactics of al-Qa'ida. No matter how the internal situation in Iraq evolves, its effects on the broader region will be felt for decades, presenting new challenges and opportunities for U.S. policy. A better understanding of how regional states and nonstate actors have responded to the Iraq conflict will better prepare the United States to manage the war's long-term consequences. To that end, the authors conducted extensive fieldwork in the region and canvassed local media sources to inform their analysis. Among their key findings: The war has facilitated the rise of Iranian power in the region, but Iran faces more limits than is commonly acknowledged; the war has eroded local confidence in U.S. credibility and created new opportunities for Chinese and Russian involvement; the war has entrenched and strengthened neighboring Arab regimes while diminishing the momentum for political reform; and the war has eroded al-Qa'ida's standing in the region, but the network and its affiliates are adapting with new tactics and strategies.